Make Way for Beauty: The Role of Contemplative Artistic Practice in Navigating Religious Education along the Unknowing Path - Triasmoroadi, Hardiyan (Theologia in Loco, 2023)
The pandemic has plunged us into a liminal situation and led us into an unknown situation. In this article, I propose an apophatic approach to cultivating spirituality in response to this prevailing uncertainty. Within the Christian spiritual tradition, two major approaches exist, i.e. the cataphatic (via affirmation) and the apophatic (via negation). While religious education often leans heavily towards the cataphatic approach rather than apophatic, I argue that in the face of uncertainty, religious education would benefit greatly from embracing the apophatic approach. One way to achieve this is by creating more space for artistic practices. Contemplative artistic practices, which yearn to find beauty apophatically, play a significant role in navigating religious education through uncertain times. The inclusion of artistic practices in religious education can deepen spirituality, help individuals navigate uncertainty, and enable them to find beauty amidst unknowing paths.